2009
DOI: 10.1002/cbf.1541
|View full text |Cite
|
Sign up to set email alerts
|

Glucose deprivation increases nuclear DNA repair protein Ku and resistance to radiation induced oxidative stress in human cancer cells

Abstract: Recent studies have indicated that nutrient deprivation particularly glucose may play a major role in tumor cell tolerance to a generally oxidative stress environment in solid tumors. Here, we studied the impact of glucose deprivation on the response of human colon (HT29)0020and prostate (DU145) cancer cells to γ radiation. A significant decrease in intracellular glucose level was observed in glucose deprived cells as measured by bioreductive assay. The survival of HT29 and DU145 were increased by 30 and 100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
(64 reference statements)
0
16
1
Order By: Relevance
“…The intracellular non protein thiol (NPSH) was determined by DTNB assay as described previously (Li et al, 2009). Cells in the dish with the desired medium were rinsed twice and the attached cells were mixed with 1 ml of ice cold 50 mM SSA buffer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intracellular non protein thiol (NPSH) was determined by DTNB assay as described previously (Li et al, 2009). Cells in the dish with the desired medium were rinsed twice and the attached cells were mixed with 1 ml of ice cold 50 mM SSA buffer.…”
Section: Methodsmentioning
confidence: 99%
“…This modification of the Active Motif nuclear extract preparation is necessary to avoid the reversal of HEDS mediated oxidation of protein thiols including Ku protein thiols by DTT (Ayene et al 2002). The nuclear proteins were prepared by membrane disruption using Active Motif hypotonic buffer, detergent and complete lysis buffer and centrifugation as per the manufacturer’s instructions (Li et al, 2009). The nuclear proteins were stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other proteins related to DNA damage were also downregulated in HUVEC treated with 400 mol/L elaidic acid, such as XRCC 5 (spot (23)), PSME 3 (spot (3)), and SAE 1 (spot (20)). XRCC 5 , a subunit of the Ku heterodimer protein, played a major role in cellular resistance to radiation [52]. However, the expression of P53 was increased ( Figure 5); this indicated that the DNA damage level was increased.…”
Section: Effect Of Elaidicmentioning
confidence: 99%
“…We have recently demonstrated in a series of publications that GSH recycling (GSH → GSSG (oxidized GSH) → GSH), which is dependent on several GSH dependent pathways, is required for the metabolic conversion of hydroxyethyldisulfide (HEDS) into mercaptoethanol (ME) (Ayene, Biaglow, Kachur, Stamato, & Koch, 2008; Ayene, et al, 2000; Ayene, et al, 2002; Biaglow, et al, 2003; Biaglow, et al, 2000; Biaglow, et al, 2006; Biaglow, et al, 1998; Li, Ayene, Ward, Dayanandam, & Ayene, 2009; Li, et al, 2013; Li, Zhang, Ward, Prendergast, & Ayene, 2012; Tuttle, et al, 2007). Unlike all the previous assays that measured just the glutathione level, a functional assay for glutathione such as HEDS metabolism will measure the “GSH dependent antioxidant capacity” of cells, a process that requires “glutathione recycling” by oxidative pentose phosphate cycle (OPPC) in conjunction with other GSH dependent pathways (Ayene, et al, 2002; Biaglow, et al, 2003; Lushchak, 2012).…”
Section: Introductionmentioning
confidence: 99%